A Social-Ecological Approach to Studying Variation in Urban Trees and Ecosystem Services in the National Municipal District of Santo Domingo, Dominican Republic - Meléndez-Ackerman, Elvia J.; Pérez, Mervin E.; Espinal, Ana B. Pou; Caballero, Claudia; Cortés, Leonardo; Bonilla-Duarte, Solhanlle; Bauer, Gerald; Martínez Guridy, José M.; Arendt, Wayne J.; Nowak, David J. (Frontiers in Sustainable Cities, 2022)
Maintaining a diverse urban forest that provides ecosystem services to city dwellers is important in promoting urban sustainability and resilience to environmental change. Many cities around the world have taken to inventorying their urban forests and quantifying their ecosystem services but these activities have been more pronounced in industrialized counties and less pronounced in Latin America. Here we described the results of an i-Tree inventory that established 206 survey plots in the National Municipal District of Santo Domingo (NMDSD). We used social-ecological theory to evaluate the potential factors that may influence urban forest structure, composition and, ecosystem services diversity across three wards with distinct social and urban characteristics. Rarefaction curves showed a diverse urban forest dominated by non-native trees that have ornamental and medicinal uses. Wards differed in species composition with palms being particularly dominant in Wards 1 and 2 where the proportion of low-income houses is lower. On average, we found no significant differences among wards in tree species richness, average dbh, leaf area, and percent tree cover per plot. Trees in Ward 2 were taller, on average, than those in Ward 1 but were similar to those in Ward 3. Likewise, tree density per plot was highest in Ward 2, followed by Ward 1 and Ward 3. Despite these significant differences in stem densities, average values in four ecosystem services involving measures of carbon, rainfall, and contaminants (C sequestration, C storage, avoided runoff, and removal of air pollutants) were non-significant across wards. We found disproportionately more street trees in Ward 1 relative to Wards 2 and 3 and more trees in public spaces in Wards 1 and 2 relative to Ward 3. Evidence for the luxury effect on tree distribution in the NMDSD was subtle and manifested mostly through differences in species composition and tree distribution across public and private domains as well as the amount of planting space. We discuss the implications of these differences and overall results for species composition within the context of urban forest management recommendations.